Water worries: An intersectional feminist political ecology of tourism and water in Labuan Bajo, Indonesia. (November 2017) - Cole, Stroma
Highlights: Presents gendered analysis of the impact of tourism on water resources. First intersectional analysis of tourism and water scarcity at the destination level. Different groups struggle daily, paying for a disproportionate share of tourisms impact. Cross fertilises Feminist Political Ecology into tourism studies. Abstract: Framed in feminist political ecology, this paper presents an intersectional analysis of the gender-water-tourism nexus. Based in an emergent tourism destination, Labuan Bajo, Indonesia, it goes beyond an analysis of how women bear the brunt of burdens related to water scarcity, and examines which women and why and how it affects their daily lives. Based on ethnographic research and speaking to over 100 respondents, the analysis unpicks how patriarchal cultural norms, ethnicity, socio-economic status, life-stage and proximity to water sources are intertwined to (re)produce gendered power relations. While there is heterogeneity of lived experiences, in the most part tourism is out competing locals for access to water leading to women suffering in multiple ways.